Analysis of Optimization of Cross-Sections and Reinforcement of Building Structures Based on SNI 2847-2019 and SNI 1726-2019 - Rizik, Ahmad Farhan; Soelarso, Soelarso; Baehaki, Baehaki; Darwis, Zulmahdi (JURUSAN TEKNIK SIPIL, 2024)
Efficiency in structural design is important to optimize the use of materials and costs, while maintaining strength and stability to ensure the safety of the building. With construction design regulations constantly updated, careful and precise planning calculations are crucial. This study identifies overdesign in columns, beams, and foundations of existing buildings, and aims to determine more optimal and efficient dimensions and repetitions, resulting in stronger, more economical, and standard-compliant buildings. The research was conducted in a 4-storey office building with dimensions of 32 x 15,725 meters will be analyzed based on SNI 2847:2019, SNI 1726:2019, and SNI 1727:2020. The analysis was carried out using Microsoft Excel and ETABS. The results of the study showed that there was overdesign in the main column, main beam, and foundation. On a beam of 400mm x 650mm it produces an efficiency of 17.46%. The bending reinforcement requirement results in an efficiency of 21.785%. Meanwhile, the shear reinforcement and middle reinforcement are the same as the initial planning. In a 450mm x 700mm column it produces an efficiency of 16%. For shear reinforcement, an efficiency of 10% is obtained. As for the bending reinforcement, it is the same as the initial planning. In the foundation design, 4 square piles with dimensions of 450mm x 450mm and pilecap dimensions of 2600mm x 2600mm x 500mm with reinforcement requirements for the x direction D22-100 and the y direction D22-125. Resulting in a pilecap volume efficiency of 28.888%.